EFFECT OF HARVESTING PRACTICES, LIFTING TIME, CURING AND IRRIGATION ON QUERCETIN CONTENT IN ONION (ALLIUM CEPA L.) CULTIVARS - Nile, Shivraj Hariram; Ko, Eun Young; Sharma, Kavita (Emirates Journal of Food and Agriculture, 2016)
The aim present study was to measure the quercetin and quercetin glucoside content in onion cultivars with respect to pre and postharvest treatments including lifting time, drip irrigation, curing and forced curing on quercetin content in nineteen onions (Allium cepa L.) cultivars were studied. The quercetin contents ranged from 0.011 to 4.109 mg/100 mg dry weight basis among nineteen studied onion varieties. The highest amount of quercetin was detected in red varieties ('Colossus‘), lowest in white varieties ('ISI 2120'), meanwhile yellow variety T-M-8-4 exhibited higher quercetin content compared to other yellow and white varieties. The amount of quercetin glucosides content in different parts of onion follows an increasing order from inner to outer scales. It has been observed that, outer scales of onions contain 3.5 times higher quercetin glucosides than the inner ones. There is no direct relation between the numbers of drip irrigation on the contents of quercetins; compared to the control group (with regular irrigation after every week). Similarly, Lifting time had minor effects on quercetin content among the selected onion cultivars. Cultivar differences in quercetin content were significant but not consistent during the time of this study. During forced curing of skin, as well as the peeled onion, the total quercetin content of cured onion decreased as compared to non-cured control samples. This study indicates that, the onion genotypes provided to be the best way to increase quercetin content in onion bulb.